2007
DOI: 10.1124/jpet.107.126144
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Release from Presynaptic Internal Stores Is Required for Ethanol to Increase Spontaneous γ-Aminobutyric Acid Release onto Cerebellum Purkinje Neurons

Abstract: Recent data have demonstrated that ethanol increases ␥-aminobutyric acid (GABA) release in many brain regions, but little is known about the mechanism responsible for this action. Consistent with previous results, ethanol increased miniature inhibitory postsynaptic current (mIPSC) frequency at the interneuron-Purkinje cell synapse in the slice and in mechanically dissociated neurons. These data suggest that ethanol is increasing spontaneous GABA release at this synapse. It is generally accepted that ethanol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 43 publications
10
66
1
Order By: Relevance
“…In addition to having direct effects on postsynaptic receptors, EtOH has been shown to modulate GABA and glutamate release from their nerve terminals (Hendricson et al, 2004;Kelm et al, 2007;Jia et al, 2008). EtOH can enhance GABA release in hippocampal slices via a number of mechanisms: increasing spontaneous action potential firing in GABAergic interneurons, decreasing the kainate-driven firing of these neurons, and enhancing presynaptic voltagedependent Ca 2ϩ channels (VDCCs) by inhibiting the voltagedependent K ϩ channels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having direct effects on postsynaptic receptors, EtOH has been shown to modulate GABA and glutamate release from their nerve terminals (Hendricson et al, 2004;Kelm et al, 2007;Jia et al, 2008). EtOH can enhance GABA release in hippocampal slices via a number of mechanisms: increasing spontaneous action potential firing in GABAergic interneurons, decreasing the kainate-driven firing of these neurons, and enhancing presynaptic voltagedependent Ca 2ϩ channels (VDCCs) by inhibiting the voltagedependent K ϩ channels.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of spontaneous and miniature GABAergic IPSCs allows investigators to determine whether the frequency of synaptic events is altered (a likely presynaptic change), or whether the amplitude is affected (likely a postsynaptic change). Such analyses have consistently shown that sISPC and mIPSC frequencies are increased at EtOH concentrations associated with intoxication, at least in the amygdala, cerebellum, hippocampus and VTA Zhu and Lovinger 2006;Theile et al 2008;Roberto et al 2003;Kelm et al 2007). These effects are rapid at onset and rapidly reversible following EtOH removal from tissue.…”
Section: Presynaptic Effects Of Ethanolmentioning
confidence: 99%
“…1). Increases in fast GABAergic synaptic transmission during EtOH treatment have been observed in cerebellum, hippocampus, ventral tegmental area (VTA), hypoglossal nucleus, and amygdala, both basolateral and central nuclei Ming et al 2006;Kelm et al 2007;Theile et al 2008;Zhu and Lovinger 2006;Roberto et al 2003;Sebe et al 2003;Ziskind-Conhaim et al 2003). These studies have been carried out mostly in brain slices and isolated brain neurons.…”
Section: Presynaptic Effects Of Ethanolmentioning
confidence: 99%
“…Ethanol enhances GABA release from presynaptic terminals, which contributes to synaptic inhibition (for reviews, see Siggins et al, 2005;Lovinger and Roberto, 2013). These data are obtained mostly from brain slices and isolated neurons from the cerebellum, HC, VTA, and amygdala (Ariwodola et al, 2003;Roberto et al, 2003;Kelm et al, 2007;Theile et al, 2008). The mechanism of ethanol enhancement of GABA release is not well established, but ethanol may interact with mechanisms involved in intracellular calcium release, increasing presynaptic calcium concentrations (Kelm et al, 2007).…”
Section: Neural Adaptations Induced By Ethanolmentioning
confidence: 99%
“…These data are obtained mostly from brain slices and isolated neurons from the cerebellum, HC, VTA, and amygdala (Ariwodola et al, 2003;Roberto et al, 2003;Kelm et al, 2007;Theile et al, 2008). The mechanism of ethanol enhancement of GABA release is not well established, but ethanol may interact with mechanisms involved in intracellular calcium release, increasing presynaptic calcium concentrations (Kelm et al, 2007). The possible role of intracellular signaling pathways in this ethanol effect is suggested by findings that GABA release is diminished in cerebellar Purkinje neurons by PKA inhibitors and in the CeA in mice lacking PKC« (Bajo et al, 2008;Kelm et al, 2008).…”
Section: Neural Adaptations Induced By Ethanolmentioning
confidence: 99%